A meso-scale layer-specific structural constitutive model of the mitral heart valve leaflets. (1st March 2016) - Zhang, Will; Ayoub, Salma; Liao, Jun; Sacks, Michael S.
Graphical abstract: Abstract: Fundamental to developing a deeper understanding of pathophysiological remodeling in mitral valve (MV) disease is the development of an accurate tissue-level constitutive model. In the present work, we developed a novel meso-scale (i.e. at the level of the fiber, 10–100 μm in length scale) structural constitutive model (MSSCM) for MV leaflet tissues. Due to its four-layer structure, we focused on the contributions from the distinct collagen and elastin fiber networks within each tissue layer. Requisite collagen and elastin fibrous structural information for each layer were quantified using second harmonic generation microscopy and conventional histology. A comprehensive mechanical dataset was also used to guide model formulation and parameter estimation. Furthermore, novel to tissue-level structural constitutive modeling approaches, we allowed the collagen fiber recruitment function to vary with orientation. Results indicated that the MSSCM predicted a surprisingly consistent mean effective collagen fiber modulus of 162.72 MPa, and demonstrated excellent predictive capability for extra-physiological loading regimes. There were also anterior-posterior leaflet-specific differences, such as tighter collagen and elastin fiber orientation distributions (ODF) in the anterior leaflet, and a thicker and stiffer atrialis in the posterior leaflet. While a degree of angular variance was observed, the tight valvular tissue ODF also left little room for any physically meaningful angular variance in fiber mechanical responses. Finally, a novel fibril-level (0.1–1 μm) validation approach was used to compare the predicted collagen fiber/fibril mechanical behavior with extant MV small angle X-ray scattering data. Results demonstrated excellent agreement, indicating that the MSSCM fully captures the tissue-level function. Future utilization of the MSSCM in computational models of the MV will aid in producing highly accurate simulations in non-physiological loading states that can occur in repair situations, as well as guide the form of simplified models for real-time simulation tools.